2020
DOI: 10.1093/mnras/staa1220
|View full text |Cite
|
Sign up to set email alerts
|

X-ray observations of luminous dusty quasars at z > 2

Abstract: We present new X-ray observations of luminous heavily dust-reddened quasars (HRQs) selected from infrared (IR) sky surveys. HRQs appear to be a dominant population at high redshifts and the highest luminosities, and may be associated with a transitional ‘blowout’ phase of black hole and galaxy co-evolution models. Despite this, their high-energy properties have been poorly known. We use the overall sample of 10 objects with XMM–Newton coverage to study the high-energy properties of HRQs at $\langle$Lbol$\rangl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 126 publications
3
23
0
Order By: Relevance
“…We remark that the log N H values quoted here are not inferred from the X-rays but from the infrared alone, using the log N H term to parametrize the torus templates by Silva et al (2004). These estimates of N H are, however, overall consistent with measures from X-rays spectroscopic studies of SDSS QSOs (Wilkes et al 2002;Urrutia et al 2005), although these are found to be significantly higher for red QSOs selected in the near-infrared (Goulding et al 2018;Lansbury et al 2020).…”
Section: Obscuration Properties Of Blue and Red Qsosupporting
confidence: 56%
See 1 more Smart Citation
“…We remark that the log N H values quoted here are not inferred from the X-rays but from the infrared alone, using the log N H term to parametrize the torus templates by Silva et al (2004). These estimates of N H are, however, overall consistent with measures from X-rays spectroscopic studies of SDSS QSOs (Wilkes et al 2002;Urrutia et al 2005), although these are found to be significantly higher for red QSOs selected in the near-infrared (Goulding et al 2018;Lansbury et al 2020).…”
Section: Obscuration Properties Of Blue and Red Qsosupporting
confidence: 56%
“…We find we can reject this hypothesis with a confidence level of 99.9% (p-value = 2×10 −5 ) and therefore conclude this difference is statistically significant. The tentative observation, supported by the KS-test, that red QSOs have lower reprocessing efficiency would hint towards a slight difference in the torus composition, possibly related to larger gas to dust fractions and a more diffuse obscuring medium (Lansbury et al 2020).…”
Section: Reprocessing Efficiencymentioning
confidence: 90%
“…Interestingly, most of the sources with both UFO and molecular outflow detections are located in the forbidden region of the N H -λ plane (Section 5). Similarly, highly dust-reddened quasars at high redshifts (z ∼ 2), as well as other populations of luminous reddened quasars, are observed to lie in the forbidden region, suggesting that they are indeed in a blowout phase (Lansbury et al 2020). On the other hand, dust obscured galaxies may be located just at the boundary between the forbidden and long-lived regions (Zou et al 2020), and could potentially represent sources at a slightly earlier evolutionary phase.…”
Section: Discussionmentioning
confidence: 91%
“…Some exceptional cases are, however, found in very luminous dusty quasars at higher redshifts (e.g. > 0.2, Lansbury et al 2020).…”
Section: Stability Of the Dusty Torus In Mrk 1239mentioning
confidence: 99%
“…Some exceptional dusty quasars at higher redshifts, e.g. > 0.2, are found to be located in the forbidden region(Lansbury et al 2020). The black circle shows the column density of the torus in Mrk 1239.…”
mentioning
confidence: 99%